Social perception from individuals to groups - Stroessner, Steven J.; Sherman, Jeffrey W. (New York Psychology Press/Taylor & Francis Group, 2015)
This volume focuses on social perception, the processing of information about people. This issue has always been central to social psychology, but this book brings together literatures that in large part have been separated by the nature of the social target that is involved. Historically, research on person perception developed quite independently from research involving perceptions of groups. Whereas the former research generally focused on the cognitive processes involved in forming impressions of individuals, research on group perception examined the content of stereotypes and the conditions under which they are used in social judgment. There was been little overlap in the theories and methods of these subfields, and different researchers were central in each. The chapters in this book highlight research and theorizing about social perception, exploring the processes involved in social perception from persons to groups. Some chapters describe work that was originally developed in person perception but is being extended to understanding groups. Other chapters illustrate how some processes studied in the domain of stereotyping also affect perceptions of individual persons. Finally, other chapters focus on variables that affect perceptions and judgments of both individuals and groups, proving opportunities for greater recognition of the common set of factors that are central to all types of social perception. This groundbreaking book highlights the research contributions of David L. Hamilton, whose research has played a central role in uniting these previously independent areas of research. It provides essential reading for upper-level courses on social cognition or social perception and could also serve as an auxiliary text in courses on interpersonal perception/relations and courses on stereotyping/intergroup relations. --Provided by publisher.
Keywords: Social perception; Stereotypes (Social psychology)